2013
DOI: 10.1002/pd.4107
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chorionicity on first‐trimester nuchal translucency screening in ART twin pregnancies

Abstract: Measurement of NT thickness in DC ART twins achieves comparable results with twins conceived spontaneously. Conclusions in MC twins are limited; however, higher NT MoM was not related to TTTS or selective intrauterine growth restriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
2
4
1
Order By: Relevance
“…In a previous study, our group did not find a statistically significant difference in median or mean NT‐MoM values between a small number of ART pregnancies ( n = 128) and spontaneous twin pregnancies ( n = 70). Four other studies, all relatively small, have addressed the issue (Table ), one reporting a statistically significant reduction in NT for ART pregnancies and one, as the current study, a statistically significant increase. Two of these studies reported average NT separately for cases of IVF and ICSI and there were no consistent differences (Table ).…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…In a previous study, our group did not find a statistically significant difference in median or mean NT‐MoM values between a small number of ART pregnancies ( n = 128) and spontaneous twin pregnancies ( n = 70). Four other studies, all relatively small, have addressed the issue (Table ), one reporting a statistically significant reduction in NT for ART pregnancies and one, as the current study, a statistically significant increase. Two of these studies reported average NT separately for cases of IVF and ICSI and there were no consistent differences (Table ).…”
Section: Discussioncontrasting
confidence: 38%
“…Four other studies, all relatively small, have addressed the issue (Table ), one reporting a statistically significant reduction in NT for ART pregnancies and one, as the current study, a statistically significant increase. Two of these studies reported average NT separately for cases of IVF and ICSI and there were no consistent differences (Table ).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Pregnancies were classified according to the mode of conception as spontaneous vs IVF or ICSI (IVF/ICSI). Pregnancies resulting from ovulation induction were not included in the analysis in order to create a more homogeneous study group and facilitate comparison with earlier published series 13,14,16,28 . Women who conceived after insemination in a natural cycle, without ovulation induction, were included in the spontaneous-conception group, and women who conceived after egg donation were included in the IVF/ICSI group.…”
Section: Population and Data Collectionmentioning
confidence: 99%
“…It is uncertain how IVF affects the outcome of monochorionic twin pregnancies, which are already at higher risk of adverse pregnancy outcome than dichorionic pregnancies because of the presence of vascular anastomoses and potential transfusion imbalances 12 . Given its increased use, it is essential to understand better whether IVF further affects the outcome of these twins; however, the findings of studies on this topic are inconsistent [13][14][15] . Some authors have suggested lower survival rates in monochorionic diamniotic (MCDA) twins after IVF, but their results failed to show statistical significance, most probably owing to small sample size 14,16,17 .…”
Section: Introductionmentioning
confidence: 99%